High-level production of free fatty acids from lignocellulose hydrolysate by co-utilizing glucose and xylose in yeast - Xin Ni; Jingjing Li; Wei Yu; Fan Bai; Zongbao K. Zhao; Jiaoqi Gao; Fan Yang; Yongjin J. Zhou (Synthetic and Systems Biotechnology)
Lignocellulose bio-refinery via microbial cell factories for chemical production represents a renewable and sustainable route in response to resource starvation and environmental concerns. However, the challenges associated with the co-utilization of xylose and glucose often hinders the efficiency of lignocellulose bioconversion. Here, we engineered yeast Ogataea polymorpha to effectively produce free fatty acids from lignocellulose. The non-oxidative branch of the pentose phosphate pathway, and the adaptive expression levels of xylose metabolic pathway genes XYL1, XYL2 and XYL3, were systematically optimized. In addition, the introduction of xylose transporter and global regulation of transcription factors achieved synchronous co-utilization of glucose and xylose. The engineered strain produced 11.2 g/L FFAs from lignocellulose hydrolysates, with a yield of up to 0.054 g/g. This study demonstrated that metabolic rewiring of xylose metabolism could support the efficient co-utilization of glucose and xylose from lignocellulosic resources, which may provide theoretical reference for lignocellulose biorefinery.